An Experimental Investigation of Passive Variable-Pitch Vertical-Axis Ocean Current Turbine - Ridho Hantoro; I.K.A.P Utama; Erwandi Erwandi; Aries Sulisetyono (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
Vertical-axis hydrokinetic turbines with fixed pitch blades typically suffer from poor starting torque, low efficiency and shaking due to large fluctuations in both radial and tangential force with azimuth angle. Maximizing the turbine power output can be achieved only if the mechanism of generation of the hydrodynamic force on the blades is clearly identified and tools to design high-performance rotors are developed.This paper describes an initial experimental investigation to understand more of the performance on vertical-axis turbine related to the effect of fixed-pitch and passive variable-pitch application using airfoil NACA 0018. Comparative analysis according to aspects of rotation and tip speed ratios was discussed. Information regarding the changes of foil position in passive variable-pitch during rotation at a limited range of flow velocity variations test was obtained and analyzed.